Using Songs To Reinforce The Learning Of Subject-Verb Agreement - Hashim, Affendi; Abd Rahman, Shazwani (2010)
Malaysian students have always faced difficulty in understanding subject-verb agreement(SVA). The reason for this to happen is because of interference from students’ first language (L1).However, explicit teaching of this grammar point may increase students’ level of anxiety. Therefore,teachers need to camouflage the teaching by including fun elements in the lesson. Thus, this study aims toinvestigate the effectiveness of using songs in enhancing the understanding of SVA. The study adoptedquasi-experimental design. Thirty-seven primary five pupils from Sekolah Kebangsaan Sri Pulai wereinvolved. They were divided into two groups, the experimental group and the control group. Theexperimental group went through the song-based tasks in three different sessions while the control groupresumed normal lesson. The instruments used in collecting data were pre-test, post-test, observation of thetreatments from a recorded tape, and students’ reflection sheet. Data were analyzed qualitatively andquantitatively. The findings showed that song-based activities are useful tools to reinforce the learning ofSVA and provide an enjoyable classroom atmosphere. Hence, it is highly recommended that languageteachers incorporate songs in grammar lesson.